Hadith #2234 - Sunan Abi Dawud - Aisha bint Abi Bakr; al-Aswad bin Yazid الأسود بن يزيد بن قيس النخعي; Ibrahim al-Nakha'i إبراهيم النخعي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Muhammad bin Kathir al-'Abdi محمد بن كثير العبدي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
A’ishah said “The Prophet (ﷺ) gave her choice. Her husband was a slave.”
Grade: Sahih

Hadith #2308 - Sunan Abi Dawud - Aisha bint Abi Bakr; al-Aswad bin Yazid الأسود بن يزيد بن قيس النخعي; Ibrahim al-Nakha'i إبراهيم النخعي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
Do not confuse us about his Sunnah. Ibn al-Muthanna said: The Sunnah of our Prophet (ﷺ) is that the waiting period of a slave-mother whose husband has died is four months and ten days.
Grade: Sahih

Hadith #2381 - Sunan Abi Dawud - Aisha bint Abi Bakr; al-Aswad bin Yazid الأسود بن يزيد بن قيس النخعي; Alqama bin Qays علقمة بن قيس بن عبد الله; Ibrahim al-Nakha'i إبراهيم النخعي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
That Abu ad-Darda’ narrated to him: The Messenger of Allah (ﷺ) vomited and broke his fast. Then I met Thawban, the client of the Messenger of Allah (ﷺ), in the mosque in Damascus, I said (to him): Abu al-Darda has told me that the Messenger of Allah (ﷺ) vomited and broke his fast. He said: He spoke the truth ; and I poured out water for his ablution (ﷺ).
Grade: Sahih

Hadith #2438 - Sunan Abi Dawud - Aisha bint Abi Bakr; al-Aswad bin Yazid الأسود بن يزيد بن قيس النخعي; Ibrahim al-Nakha'i إبراهيم النخعي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: There is no virtue more to the liking of Allah in any day than in these days, that is, the first ten days of Dhu al-Hijjah. They (the Companions) asked: Messenger of Allah, not even the struggle in the path of Allah (Jihad) ? He said: (Yes), not even the struggle in the path of Allah, except a man who goes out (in the path of Allah) with his life and property, and does not return with any of them.
Grade: Sahih

Hadith #2763 - Sunan Abi Dawud - Aisha bint Abi Bakr; al-Aswad bin Yazid الأسود بن يزيد بن قيس النخعي; Ibrahim al-Nakha'i إبراهيم النخعي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Sufyan bin 'Uyaynah سفيان بن عيينة; Uthman bin Muhammad (Sunan Abi Dawud)
Ibn ‘Abbas said “Umm Hani daughter of Abu Talib told me that in the year of the conquest she gave protection to a man from the polytheists. She came to the Prophet (ﷺ) and mentioned it to him. He said “We have given security to those to whom you have given it.”
Grade: Sahih

Hadith #2892 - Sunan Abi Dawud - Aban bin Tghlb أبان بن تغلب; al-Aswad bin Yazid الأسود بن يزيد بن قيس النخعي; Mu'adh ibn Jabal; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Qatada قتادة (Sunan Abi Dawud)
The wife of Sa’d b. al-Rabi said: Messenger of Allah, Sa’d died and left two daughters. He then narrated the rest of the tradition in a similar way. Abu Dawud said: This is the most correct tradition.
Grade: Hasan

Hadith #2915 - Sunan Abi Dawud - Aisha bint Abi Bakr; al-Aswad bin Yazid الأسود بن يزيد بن قيس النخعي; Ibrahim al-Nakha'i إبراهيم النخعي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Uthman bin Muhammad; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Abi Dawud)
‘Aishah, mother of believers (ra), intended to buy a slave-girl to set her free. Her people said: We shall sell her to you on one condition that we shall inherit from her. ‘Aishah mentioned it to the Messenger of Allah (ﷺ). He said: That should not prevent you, for the right of inheritance belongs to the one who has set a person free.
Grade: Sahih

Hadith #3879 - Sunan Abi Dawud - Aisha bint Abi Bakr; al-Aswad bin Yazid الأسود بن يزيد بن قيس النخعي; Ibrahim al-Nakha'i إبراهيم النخعي; Jarir bin 'Abdul Hameed al-Razi جرير بن عبد الحميد أبو عبد الله الضبي; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Uthman bin Muhammad (Sunan Abi Dawud)
The evil is genuine.
Grade: Sahih

Hadith #3993 - Sunan Abi Dawud - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; al-Aswad bin Yazid الأسود بن يزيد بن قيس النخعي; Hafs bin 'Umar bin al-Harith حفص بن عمر بن الحارث; ibn Mas'ud; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) made me read the verse “It is I who give (all) sustenance, Lord of power, steadfast (for ever).
Grade: Sahih

Hadith #4396 - Sunan Abi Dawud - Aisha bint Abi Bakr; al-Aswad bin Yazid الأسود بن يزيد بن قيس النخعي; Hammad bin Salama حماد بن سلمة; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Ibrahim al-Nakha'i إبراهيم النخعي; Uthman bin Muhammad; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
A woman borrowed jewellery through some known persons and she herself was unknown. She then sold them. She was seized and brought to the Prophet (ﷺ). He gave orders that her hand should be cut off. It is this woman about whom Usamah interceded and of her the Messenger of Allah (ﷺ) said whatever he said.
Grade: Sahih

Hadith #4466 - Sunan Abi Dawud - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; al-Aswad bin Yazid الأسود بن يزيد بن قيس النخعي; Alqama bin Qays علقمة بن قيس بن عبد الله; Ibrahim al-Nakha'i إبراهيم النخعي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Smak bin Hrb bin Aws سماك بن حرب بن أوس (Sunan Abi Dawud)
A man came to the Prophet (ﷺ) and made acknowledgment before him that he had committed fornication with a woman whom he named. The Messenger of Allah (ﷺ) sent someone to the woman and he asked her about it. She denied that she had committed fornication. So he gave him the prescribed punishment of lashes and left her.
Grade: Sahih

Hadith #4550 - Sunan Abi Dawud - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; al-Aswad bin Yazid الأسود بن يزيد بن قيس النخعي; Alqama bin Qays علقمة بن قيس بن عبد الله (Sunan Abi Dawud)
‘Umar gave judgement that bloodwit for quasi-intentional murder should be thirty she-camels in their fourth year, thirty she-camels in their fifth year, and forty pregnant she-camels in their sixth year up to the ninth
Grade: Da'if